GPR30 regulates the EGFR-Akt cascade and predicts lower survival in patients with ovarian cancer - Fujiwara Satoe; Terai Yoshito; Kawaguchi Hiroshi; Takai Masaaki; Yoo Saha; Tanaka Yoshimichi; Tanaka Tomohito; Tsunetoh Satoshi; Sasaki Hiroshi; Kanemura Masanori; Tanabe Akiko; Yamashita Yoshiki; et al. (BMC, 2012)
Abstract Objectives G protein-coupled receptor 30 (GPR30) is a 7-transmembrane estrogen receptor that functions alongside traditional estrogen receptors to regulate the cellular responses to estrogen. Recent studies suggest that GPR30 expression is associated with a poor prognosis, and that this is due to the GPR30-mediated transactivation of the EGFR in breast cancer. However, the biological contribution of GPR30 in ovarian cancer remains unclear. The purpose of this study was to elucidate the relationships between GPR30 expression and the clinicopathological findings, and to determine how the signaling cascade influences the prognosis of ovarian cancer. Methods The expression levels of GPR30, EGFR, ERα, and ERβ were analyzed using an immunohistochemical analysis, and their correlations with the clinicopathological features were examined in 10 patients with borderline malignant tumors and 152 patients with epithelial ovarian cancer. We also examined whether GPR30 signaling activates the EGFR-Akt pathway in an ovarian cancer cell line (Caov-3) by a Western blotting analysis. Results The GPR30 expression in ovarian carcinomas was significantly higher than that in borderline malignancies (p=0.0016), and was not associated with the expression of the EGFR, ERα, or ERβ. The expression of GPR30 in clear cell carcinomas was significantly lower than that in other subtypes of cancer (P <; 0.001). The expression of both GPR30 and EGFR was significantly associated with a poor prognosis in terms of the progression-free survival rate. The phosphorylation of the EGFR and Akt could be significantly enhanced by G1 (p <; 0.05) and inhibited by a Src family kinase inhibitor. Conclusion The expression of both GPR30 and EGFR is associated with a poor outcome in ovarian cancer, and GPR30 increases the phosphorylation of Akt via the EGFR in ovarian cancer cells. The regulation of GPR30 might be a potentially useful new therapeutic target in ovarian cancer.